Inovasi Pembelajaran Bumi dan Tata Surya Melalui Virtual Reality (VR) di CoSpace Edu - Rahman, Muhammad Arif; Suwarna, Iwan Permana; Romadhon, Dzikri Rahmat (PAKAR Pendidikan, 2024)
This research aims to improve junior high school student's understanding of the earth and solar system concept through virtual reality (VR) in CoSpace Edu through a Research and Development (RnD) approach with the 4D model (Define, Design, Develop, Disseminate), the research was conducted in several junior high schools in Depok, involving physics teachers and students in grades 8 and 9. The need for interactive media that can visualize the concept of the solar system and the eclipse phenomenon was observed through preliminary studies in the form of observations and interviews. The development of this VR media begins with a needs analysis, followed by design, product development, and deployment. Data collection instruments include observation, interviews, questionnaires, and tests. Data analysis is based on questionnaires from experts, teachers, and students and media effectiveness tests using N-Gain calculations. Based on the N-gain calculation, a score of 0.624 was obtained in the small group and 0.505 in the field test. The results showed that using VR media effectively improves the understanding of the concept of the earth and solar system, contributing to understanding the concept of the earth and solar system